(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The word financial literacy has led to the publication of financial literacy eras in many countries. The scope and methods of parcels vary greatly from country to country. In India, they want financial literacy to grow due to low literacy rates and a large population that is excluded from formal monetary policy. This article aims is to draw sketch for the high profile of financial knowledge as well as awareness in India through various research findings and various financial training packages launched in India to increase financial literacy in India. There are also some tips to make our money education packages more effective. Financial literacy has become especially important in recent years as the literacy play crucial role in to understand the financial structures of the 21st century have evolved rapidly and become more complex and global.